Astrocyte EV-Induced lincRNA-Cox2 Regulates Microglial Phagocytosis: Implications for Morphine-Mediated Neurodegeneration - Guoku Hu; Ke Liao; Fang Niu; Lu Yang; Blake W. Dallon; Shannon Callen; Changhai Tian; Jiang Shu; Juan Cui; Zhiqiang Sun; Yuri L. Lyubchenko; Minhan Ka; et al. (Elsevier, 2018)
Impairment of microglial functions, such as phagocytosis and/or dysregulation of immune responses, has been implicated as an underlying factor involved in the pathogenesis of various neurodegenerative disorders. Our previous studies have demonstrated that long intergenic noncoding RNA (lincRNA)-Cox2 expression is influenced by nuclear factor κB (NF-κB) signaling and serves as a coactivator of transcriptional factors to regulate the expression of a vast array of immune-related genes in microglia. Extracellular vesicles (EVs) have been recognized as primary facilitators of cell-to-cell communication and cellular regulation. Herein, we show that EVs derived from astrocytes exposed to morphine can be taken up by microglial endosomes, leading, in turn, to activation of Toll-like receptor 7 (TLR7) with a subsequent upregulation of lincRNA-Cox2 expression, ultimately resulting in impaired microglial phagocytosis. This was further validated in vivo, wherein inhibition of microglial phagocytic activity was also observed in brain slices isolated from morphine-administrated mice compared with control mice. Additionally, we also showed that intranasal delivery of EVs containing lincRNA-Cox2 siRNA (small interfering RNA) was able to restore microglial phagocytic activity in mice administered morphine. These findings have ramifications for the development of EV-loaded RNA-based therapeutics for the treatment of various disorders involving functional impairment of microglia. Keywords: phagocytosis, drug abuse, morphine, extracellular vesicle, exosome, lincRNA, microglia, CNS